2015
DOI: 10.1007/s00429-015-1153-1
|View full text |Cite
|
Sign up to set email alerts
|

Galanin receptor 2-neuropeptide Y Y1 receptor interactions in the dentate gyrus are related with antidepressant-like effects

Abstract: Galanin (GAL) and the NPYY1 agonist play a role in mood regulation and both neuropeptides interact in several central functions. The present study examined the interaction between Galanin receptor 2 (GALR2) and Neuropeptide Y Y1 receptor (NPYY1R) in the dentate gyrus (DG) of the Hippocampus in relation to depression-like behavior. Using receptor autoradiography, in situ hybridization and in situ proximity ligation assay an interaction between GALR and NPYY1R was demonstrated in the DG probably involving the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…Several GALR and NPYY1R interactions were described in distinct regions of the limbic system ( Diaz-Cabiale et al, 2011 ; Narvaez et al, 2015 , 2016 ). In the amygdala, a facilitatory GALR/NPYY1R interaction was demonstrated involving the formation of GALR2/NPYY1R heteroreceptor complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Several GALR and NPYY1R interactions were described in distinct regions of the limbic system ( Diaz-Cabiale et al, 2011 ; Narvaez et al, 2015 , 2016 ). In the amygdala, a facilitatory GALR/NPYY1R interaction was demonstrated involving the formation of GALR2/NPYY1R heteroreceptor complexes.…”
Section: Introductionmentioning
confidence: 99%
“…DPN downregulates Galr2 in the hippocampus. Galanin receptor 2 interacts with neuropeptide Y Y1 receptor in the dentate gyrus and contributes to an antidepressant effect (Narvaez et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…46,73 GALRs and neuropeptide Y Y1 (NPYY1) receptor interaction may also play a role in the pathophysiology of mood disorders, including depression and anxiety. 9,[74][75][76] Narvaez et al confirmed the interaction between GalR2 and NPYY1R in the dentate gyrus (DG) with enhancement of the antidepressive-like behavior mediated by NPY Y1R 77 and anxiolytic behavior. 78 Moreover, GalR1-GalR2 heteromer interaction with Neuropeptide Y Y2 (NPYY2) may be a key molecular mechanism for GAL and its GAL1-15.…”
Section: Galanin In Depressionmentioning
confidence: 96%